Hubungan Stres dengan Mekanisme Koping Perawat ICU dalam Penanganan COVID-19 di Rumah Sakit - Liliek Fauziah; Hery Prayitno (STIKES Karya Husada Kediri, 2021)
Abstract ICU nursing services are nursing services provided to patients in critical condition in intensive care rooms, implemented in an integrated manner by a team that is trained and experienced in the field of critical care.Stress is the body's non-specific response to every need regardless of its nature.The nursing profession is prone to stress. One of the risk factors that cause nurses to become stressed is exposure to infections brought from the hospital, both bacterial and viral infections. COVID-19 is an infectious disease caused by the corona virus.This study aims to determine the relationship between stress and coping mechanisms in ICU nurses in handling COVID-19 in hospitals.This research used quantitative analytic survey with cross sectional approach. The population in this study were 27 respondents, the sampling technique used was total sampling.The instrument used was a questionnaire in the form of a google form. The bivariate analysis used was rank-spearman.The results obtained, namely p-value 0.171> 0.05, it can be concluded that there is no relationship between stress and the coping.The suggestion in this research is that the research results are expected to be input for the hospital in making policies for nurses in handling COVID-19 patients, so that they can prevent sustainable stress levels and have an adaptive coping mechanism mechanism of ICU nurses in handling COVID-19 patients at the hospital. Keywords: coping mechanism, nurse, stress